Towards large scale multi-target tracking - Vo, Ba-Ngu; Vo, Ba Tuong; Reuter, S.; Lam, Q.; Dietmayer, K. (SPIE, 2014)
Multi-target tracking is intrinsically an NP-hard problem and the complexity of multi-target tracking solutions usually do not scale gracefully with problem size. Multi-target tracking for on-line applications involving a large number of targets is extremely challenging. This article demonstrates the capability of the random finite set approach to provide large scale multi-target tracking algorithms. In particular it is shown that an approximate filter known as the labeled multi-Bernoulli filter can simultaneously track one thousand five hundred targets in clutter on a standard laptop computer. © 2014 SPIE.